The study on the use of a biocatalyst based on Calcined Cow Teeth-TiO2 composite in degrading the methylene blue dye - Khalil EL Abbadi; Fatine Echabbi; Younes Ouzidan; Amina Khalidi-Idrissi; Rajae Lakhmiri; Mohamed Safi (Results in Chemistry, 2023)
Cow teeth are a type of natural biomaterial exhibiting a unique hierarchical porous structure that has not been widely studied in catalysis. In this work, from a simple deposition and calcination process, a Cow Teeth composite CCT-TiO2 was fabricated using Calcined Cow Teeth as a template and employed as a biocatalyst to remove a specific target dye from an aqueous solution under UV irradiation.The composite, CCT-TiO2, with a dosage of (0.2 g/L), at room temperature and a 3 h treatment time under UV light, showed a positive behavior towards the photochemical degradation of Methylene Blue (C = 0.01 g/L) mainly in a basic medium pH = 8 giving a catalytic efficiency rate up to 98%.The main parameters affecting the efficiency of the photocatalytic treatment, such as pH, the mass of catalyst added to the solution, the percentage of TiO2 in the composite, the concentration of MB at the beginning, the presence of ethanol, the addition of hydrogen peroxide and the temperature were studied to evaluate their influence on the degradation of methylene blue.The photodegradation performance is inversely proportional to the initial dye concentration. Similarly, for the temperature, the higher the temperature, the higher the photodegradation performance (removal rate 57% for a temperature of 55 °C). However, the presence of ethanol in the solution has a negative impact on the oxidation process, with a yield of 56% after 4 h30 min of treatment under UV irradiation. On the other side, the addition of oxygenated water considerably improves the photodegradation performances of methylene blue, with an efficiency of dye removal going up to 87% after 1 h of treatment.The excellent catalytic degradation performance and low cost suggest that this process has significant potential for effectively treating industrial wastewater loaded with cationic dye.